Avidity of anti-P aeruginosaantibodies during chronic infection in patients with cystic fibrosis. Issue 2 (1st February 1999) - Ciofu, Oana; Petersen, Tine D; Jensen, Per; Høiby, Niels
Abstract : BACKGROUND: In order to study the impact on the lung function of patients with cystic fibrosis of the avidity of antipseudomonal antibodies, the avidity of antibodies against the chromosomal β-lactamase of Pseudomonas aeruginosa (aβab) and against the 60–65 kDa heat shock protein of P aeruginosa (anti-GroEL) were measured in serum samples collected longitudinally during chronic infection with P aeruginosa from a group of patients with poor and good lung function. METHODS: The thiocyanate elution method in which the molarity of potassium thiocyanate required to elute 50% bound antibody under conditions of antigen excess in ELISA was used to measure the relative avidity. RESULTS: All patients developed increasing levels of aβab and anti-GroEL antibodies during the follow up period but no maturation of the avidity of these antibodies was observed. In patients with good lung function the avidity of aβab was higher than in patients with poor lung function (p = 0.018). No significant difference in the avidity of the anti-GroEL antibodies was observed between the two groups of patients. CONCLUSION: In patients with cystic fibrosis a high avidity of aβab could contribute to a more efficient inhibition of the β-lactamase by these antibodies, resulting in the better lung function seen in this group. The immunopathological implication of the failure in avidity maturation of antibodies in chronic infection is discussed.